Methods of Developing Students’ Critical Thinking Skills in Online and Distance Education - Mirzayeva, Nasiba (The Lingua Spectrum, 2025)
This article analyzes methods for developing students’ critical thinking skills in online and distance education environments and describes effective approaches that can be implemented by educators. The study emphasizes the growing importance of interactive and learner-centered strategies as essential tools for promoting active engagement in virtual classrooms. It highlights how problem-based learning, discussion forums, case studies, and digital simulations create opportunities for learners to question, evaluate, and synthesize information rather than passively receive knowledge. The analysis also considers the role of collaborative platforms, such as group projects and peer feedback, which foster cooperation and the exchange of diverse perspectives, thereby encouraging reflective thinking. Furthermore, the paper examines how innovative technologies – such as online conferencing tools, learning management systems, and AI-driven applications – provide flexible and accessible means for critical inquiry. The findings demonstrate that integrating these methods into distance learning can significantly enhance the development of critical thinking skills, making students more independent, analytical, and adaptable in both academic and professional contexts.